The Diagnostic Value of Serum GDF15 and hs-CTnT in Elderly Patients with Acute Myocardial Infarction. (20th May 2022) - He, Yejun; Wang, Hui; Fang, Zhihua
Abstract : Objective . To analyze the diagnostic value of serum growth differentiation factor 15 (GDFl5) and high-sensitivity troponin T (hs-cTnT) in elderly acute myocardial infarction (AMI). Methods . A retrospective analysis of 165 patients with acute chest pain admitted to the Department of Cardiology in our hospital from January to December 2020, Among them, 76 AMI patients (AMI group), 89 non-AMI patients (non-AMI group), and 80 healthy people were selected as the control group during the same period. Compare the three groups of serum GDF15, hs-CTnT levels, and left ventricular ejection fraction (LVEF) parallel correlation analysis, and draw the receiver operating curve (ROC) of serum GDF15 and hs-CTnT levels to diagnose AMI. Results . The serum GDF15 and hs-CTnT levels of the AMI group were significantly higher than those of the non-AMI group and the control group, and the difference was statistically significant (p < 0.01). The LVEF was significantly lower than the non-AMI group and the control group, whose difference was statistically significant (p < 0.01). Among them, the indicators of the non-AMI group were both higher and lower than the control group, and the difference was statistically significant (p < 0.01). Serum GDF15 and hs-CTnT levels of AMI patients increased with the increase of NYHA grade, among which grade IV group was significantly higher than grade I∼II group and grade III group ( P < 0.01), and grade III group was significantly higher than grade I∼II Group (p < 0.01). Pearson correlation analysis showed that GDF15 and hs-CTnT levels of AMI patients were significantly negatively correlated with LVEF ( r = −0.584, −0.612, − < 0.01). The ROC curve showed that GDF15 had a high specificity (93.75%) and hs-CTnT has a high sensitivity (90.67%). The area under the curve for diagnosing AMI is > 0.7 (0.895, 0.948). The sensitivity of the combined detection and the specificity are higher than that of individual detection. Conclusion . Serum GDF15 and hs-CTnT are highly expressed in elderly patients with AMI. The combined detection of the two can improve the efficiency of AMI diagnosis. GDF15 can be used as a new biomarker for AMI diagnosis and disease monitoring.